DNA damage response curtails detrimental replication stress and chromosomal instability induced by the dietary carcinogen PhIP. Issue 21 (5th September 2016) - Mimmler, Maximilian; Peter, Simon; Kraus, Alexander; Stroh, Svenja; Nikolova, Teodora; Seiwert, Nina; Hasselwander, Solveig; Neitzel, Carina; Haub, Jessica; Monien, Bernhard H.; Nicken, Petra; Steinberg, Pablo; et al.
Abstract: PhIP is an abundant heterocyclic aromatic amine (HCA) and important dietary carcinogen. Following metabolic activation, PhIP causes bulky DNA lesions at the C8-position of guanine. Although C8-PhIP-dG adducts are mutagenic, their interference with the DNA replication machinery and the elicited DNA damage response (DDR) have not yet been studied. Here, we analyzed PhIP-triggered replicative stress and elucidated the role of the apical DDR kinases ATR, ATM and DNA-PKcs in the cellular defense response. First, we demonstrate that PhIP induced C8-PhIP-dG adducts and DNA strand breaks. This stimulated ATR-CHK1 signaling, phosphorylation of histone 2AX and the formation of RPA foci. In proliferating cells, PhIP treatment increased the frequency of stalled replication forks and reduced fork speed. Inhibition of ATR in the presence of PhIP-induced DNA damage strongly promoted the formation of DNA double-strand breaks, activation of the ATM-CHK2 pathway and hyperphosphorylation of RPA. The abrogation of ATR signaling potentiated the cell death response and enhanced chromosomal aberrations after PhIP treatment, while ATM and DNA-PK inhibition had only marginal effects. These results strongly support the notion that ATR plays a key role in the defense against cancer formation induced by PhIP and related HCAs.